ALINEA Storybook: Enhancing Understanding of Local Cultural Values - Kustyamegasari, Arista; Gunansyah, Ganes; Mariana, Neni (Jurnal Pendidikan Edutama, 2025)
Indonesia's cultural diversity is reflected in numerous traditions, such as the Rokat Tase' ceremony in Madura, which embodies moral values like cooperation, gratitude, and environmental conservation. However, integrating local culture into educational contexts remains challenging. This study explores the use of the ALINEA storybook and culturally-themed worksheets to enhance students' understanding of local cultural values, particularly through the Rokat Tase' tradition. A qualitative descriptive approach was employed, involving observations, semi-structured interviews, and contextual learning activities at SDN Junganyar 1 Socah. Data were analyzed thematically, focusing on student engagement, cultural comprehension, and connections to everyday life. The ALINEA storybook effectively introduced students to cultural values such as cooperation and gratitude, helping them relate these values to their daily experiences. Students demonstrated active participation in discussions and creative activities like poster-making, while teachers acknowledged the relevance and practicality of the media despite minor challenges in language comprehension. This study highlights the potential of ethnosocial learning tools in integrating local traditions into formal education, fostering not only academic learning but also cultural preservation. These findings underscore the importance of contextually relevant teaching strategies for promoting multicultural education.